Kliniczne wskazania do operacji usunięcia gałki ocznej – przegląd piśmiennictwa - Obuchowska, Iwona; Mariak, Zofia; Sherkawey, Nebi (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Enucleation is an acceptable therapeutic modality used for end-stage ocular diseases unresponsive to another treatment. The most often indications for enucleation are trauma, intraocular tumors, secondary glaucoma, phthisis bulbi and cosmetically disfuring eyes. Although, indications for enucleation are similar in most ophthalmic clinics, the pathologic conditions leading to this procedure differ from place to place. The aim of this paper is to present the current knowledge about the clinical indications for enucleation in different parts of the world.